Mesoscale and intraseasonal air–sea CO2 exchanges in the western Arabian Sea during boreal summer. (September 2015) - Valsala, Vinu; Murtugudde, Raghu
Abstract: Intraseasonal variability, considered a coupled phenomenon, typically occurs in the 20-to-90 day-band and is seen in several of the air–sea interaction parameters over the Indian Ocean. The corresponding variability in the air–sea CO2 exchanges and oceanic pCO2 are not widely studied. In this study, we focus on the boreal summer season to find that there is a strong air–sea interaction of carbon cycle over the Somali region of the western Arabian Sea where the intraseasonal variability during this season is clearly evident in the intense variability in winds, the strength of the upwelling and the evolution of meso-scale eddies. The oceanic pCO2 variability in this intraseasonal band over the Somali region is also remarkably consistent with the other variables and is found to be driven by sea surface temperatures (SST) albeit with a counteracting but relatively minor influence from the dynamics of dissolved inorganic carbon (DIC). The 20-to-90 day-band in pCO2 accounts for about 40% of the monthly mean variability of the sea-to-air CO2 fluxes of this region in boreal summer. Ocean dynamic control on the atmospheric wind response at these mesoscales has been reported before and this study demonstrates that the ocean dynamics also control the seawater pCO2 and the air–sea CO2 fluxes in this region. Other regions with similar meso-scale dynamics must be analyzed for processes that determine air–sea CO2 exchanges and to determine whether the mesoscale fluxes contribute to the low-frequency CO2 fluxes. The role of the intraseasonal variability in atmospheric pCO2 in this exchange is not quantified here due to the lack of data at such high resolutions and needs to be considered in further observational and modeling efforts. Highlights: Intraseasonal variability (ISV) of marine pCO2 and air–sea CO2 fluxes over Arabian Sea. Over 75% of pCO2 ISV in the western Arabian Sea is induced by the variability in SST. The role of nutrient and carbon dynamics explains only below 10% of the pCO2 ISV